Lived Experiences of English Teachers in Integrating Bloom’s Digital Taxonomy on Their Differentiated Instruction Practices: A Phenomenological Study - Clara Mae E. Nava; Glen P. Cortezano; Alberto D. Yazon; Karen A. Manaig; John Frederick B. Tesoro (Magister Program of English Education, Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2022)
This qualitative research, a hermeneutic study, focused on exploring and capturing the essence and meaning of lived experiences of English teachers in integrating Bloom’s Digital Taxonomy (BDT) into their differentiated instruction practices. Bloom's Digital Taxonomy highly contributes to the change that education witnesses today. Students acquire knowledge and skills in various ways and at different speeds, and the idea of giving a personalized learning experience for students in a digital classroom is challenging. From the interviews and observations conducted, participants revealed that acceptance and self-initiated learning served as the key to adapting to technology and learning tools as anchored in BDT for the sudden paradigm shift in education. Participants considered technical aspects, digital literary skills, monitoring, and interaction as challenges to overcome and should be a part of the virtual preparedness. Moreover, teachers positively embrace and maximize the use of technology in education. BDT keeps them on track in aligning learning objectives in differentiated instruction attainable in a virtual set-up. The use of Digital tools as anchored in BDT boosts engagement and motivation, builds closer imitation of face-to-face classes, and enhances education delivery and management in a virtual environment. The researcher recommends that teachers undergo professional development focusing on BDT in differentiated instruction teaching English subjects. The education may use the MDT-EDP Training plan of this study and may conduct a needs analysis to provide the most relevant training for the educators based on their skills, needs, and interest.